Sedentary-related abdominal fat accumulation reduced by administrating heat-treated Bacillus subtilis-derived postbiotic - Wang, Mi; He, Feng; Meng, Weishuang; Chen, Zeliang; Yang, Huijie; Xu, Shi Qi; Xin, Dang De; Li, Desheng (Frontiers in Nutrition, 2025)
BackgroundA sedentary lifestyle can induce obesity, characterized by the accumulation of abdominal fat. Due to contemporary breeding practices, developing chicks exhibit increased resting time and decreased locomotor activity, resembling the sedentary lifestyle of humans. Developing chicks often show a substantial accumulation of abdominal fat and possess a digestive tract structure similar to humans. Consequently, they are widely used as experimental animal to study measures for improving intestinal health and reducing abdominal fat accumulation.MethodsIn this study, we used chicks as experimental animal to investigate the effects of administering heat-treated B. subtilis-derived postbiotic (high-temperature treated B. subtilis) on abdominal fat accumulation, hematology parameters, intestinal microbiota composition, and intestinal contents and serum metabolites composition. A total of 120 day-old chicks were randomly assigned to two groups (CON; IBS) based on their initial body weight (52.79 ± 0.60 g). Each group had 6 replicates, with each replicate containing 10 animals. Animals in the IBS group were administered 0.30% heat temperature treated-B. subtilis for 42 days. On the final day, three animals were selected from each replicate to collect abdominal fat and liver organs, serum samples, and cecal content samples for further analysis.ResultsThe results indicated that administering the postbiotic reduced abdominal fat accumulation, as well as serum total cholesterol and triglyceride levels. Moreover, heat-treated B. subtilis-derived postbiotic administration decreased the abundance of Bacteroides, Sphingomonas, and Klebsiella, while increasing Streptococcus, Veillonella, Allobaculum, and Dorea in the intestine. Metabolomic analyses revealed that administering the postbiotic reduced intestinal phosphatidylcholine and serum 13(S)-HODE levels. Spearman correlation analysis suggested a potential link between Klebsiella and Sphingomonas bacteria and these metabolites.DiscussionAs phosphatidylcholine plays a key role in facilitating intestine to absorb lipids from diet, administering heat-treated B. subtilis-derived postbiotic was therefore to be considered as an effective measure in regulating intestinal microbiota composition and their lipid metabolic activity, thereby controlling the development of obesity.